2015
DOI: 10.1007/s12410-015-9345-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cardiac MRI in Patients with Troponin-Positive Chest Pain and Unobstructed Coronary Arteries

Abstract: Acute coronary syndrome (ACS) still remains one of the leading causes of mortality and morbidity worldwide. Seven to fifteen percent of patients presenting with ACS have unobstructed coronary artery disease (CAD) on urgent angiography. Patients with ACS and unobstructed coronary arteries represent a clinical dilemma and their diagnosis and management is quite variable in current practice. Cardiovascular magnetic resonance imaging with its unique non-invasive myocardial tissue characterization property has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 72 publications
1
48
1
7
Order By: Relevance
“…(13,18) In our cohort, the most common diagnosis was MI (25%, n=97), closely followed by myocarditis (25%, n=96) and cardiomyopathy (25%). However, the literature suggests myocarditis to be much more common than MI (10)(11)(12)(13)15), contrary to our result. The mean age in our study was much higher compared to the other studies on MINOCA which may have contributed to the higher prevalence of MI.…”
Section: Diagnostic Role Of Cmr In Minocacontrasting
confidence: 99%
See 1 more Smart Citation
“…(13,18) In our cohort, the most common diagnosis was MI (25%, n=97), closely followed by myocarditis (25%, n=96) and cardiomyopathy (25%). However, the literature suggests myocarditis to be much more common than MI (10)(11)(12)(13)15), contrary to our result. The mean age in our study was much higher compared to the other studies on MINOCA which may have contributed to the higher prevalence of MI.…”
Section: Diagnostic Role Of Cmr In Minocacontrasting
confidence: 99%
“…(3) (9) Confirmation or exclusion of myocardial infarction (MI) by CMR facilitates tailoring of medical therapy, ensuring appropriate long-term secondary prevention and modification of risk, and also minimizing exposure to anti-platelet therapy and the associated bleeding risks for those with a non-coronary aetiology for the MINOCA presentation. (10). Few previous studies have shown that CMR can identify the underlying diagnosis, most commonly: acute/chronic myocarditis, acute MI with spontaneous recanalization/embolus, stress cardiomyopathy (Takotsubo) or other cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Moreover, from 7 to 15% of patients presenting with ACS had unobstructed coronaries on urgent invasive or non-invasive angiography representing a clinical dilemma, as the underlying diagnosis is variable and often unclear. 55 In this scenario, CMRI may play a consistent role in differential diagnoses of important mimickers of ACS. By using a multiparametric protocol, MRI may be particularly useful in determining the diagnosis and differentiate ischaemic from non-ischaemic causes, thereby guiding patient management.…”
Section: Echocardiographymentioning
confidence: 99%
“…These include in most of the cases (.95%) myocarditis, embolic/spontaneous recanalization myocardial infarction and Tako-Tsubo cardiomyopathy. 3,55 Since some abnormalities such as myocardial oedema/inflammation may be reversible and resolve with time, MRI scan performed at the time of acute presentation is more sensitive for diagnosis.…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation